Prevalence of cocaine use and cocaine use disorder among adult patients with attention-deficit/hyperactivity disorder: A systematic review and meta-analysis. (November 2021) - Oliva, F.; Mangiapane, C.; Nibbio, G.; Berchialla, P.; Colombi, N.; Vigna-Taglianti, F.D.
Abstract: We conducted this systematic review and meta-analysis (registered with PROSPERO CRD42020142039) of the literature to estimate the lifetime prevalence of cocaine use and cocaine use disorder among adult patients with attention-deficit/hyperactivity disorder (ADHD). The literature search was performed on the electronic databases PubMed and PsychINFO without date or language restrictions. Additional studies were identified by hand searching of citations. Inclusion criteria were: studies involving adult patients with ADHD and reporting cocaine use and/or cocaine use disorders. Data were pooled in the meta-analyses using a generalized linear mixed model with random effects. Statistical heterogeneity was assessed using the Cochran Q test. Sensitivity analyses were conducted. Twelve studies were included in the review: six in the meta-analysis of cocaine use and nine in the meta-analysis of cocaine use disorder. The estimated prevalence of cocaine use was 26.0% (95% CI 0.18–0.35) and the estimated prevalence of cocaine use disorder was 10.0% (95% CI 0.08–0.13). Heterogeneity in both meta-analyses was high but decreased to non-significance in the meta-analysis on cocaine use disorder after excluding the outlier study. In conclusion, one out of four adult patients with ADHD use cocaine and one out of ten develop a lifetime cocaine use disorder. Since cocaine use can lead to more severe and complex disorders of impaired systemic functioning, adult patients with ADHD should be assessed for cocaine use disorder and promptly referred for treatment.